2001
DOI: 10.1159/000046655
|View full text |Cite
|
Sign up to set email alerts
|

Severe Coombs’-Negative Autoimmune Hemolytic Anemia in a Kidney Transplant Patient

Abstract: Background/Aim: Few cases are found in the literature regarding autoimmune hemolytic anemia which is Coombs’ test positive in kidney transplant patients, although hemolytic uremic syndrome due to cyclosporin and FK506 has been well described. In the following, we describe a case of severe life-threatening Coombs’ test negative autoimmune hemolytic anemia after kidney transplantation. Methods: Soon after undergoing renal transplantation, the patient presented with hemolytic anemia. Kidney biopsy, routine Coombs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although the early onset of hemolysis at Day +15, the ABO nonidentical nature of the donors and the weak reactivity of DAT suggestive of low antibody titers make the etiology of PLS likely, donor attributed antibodies were not demonstrated. Other than PLS, other factors may lead to hemolysis after SOT [18][19][20][21]. Immune-mediated hemolytic anemia may be alloimmune or autoimmune.…”
Section: Discussionmentioning
confidence: 99%
“…Although the early onset of hemolysis at Day +15, the ABO nonidentical nature of the donors and the weak reactivity of DAT suggestive of low antibody titers make the etiology of PLS likely, donor attributed antibodies were not demonstrated. Other than PLS, other factors may lead to hemolysis after SOT [18][19][20][21]. Immune-mediated hemolytic anemia may be alloimmune or autoimmune.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our survey are consistent with, and expand upon, the observations from other previous studies. 13 Specifically, DAT-negative WAIHA has been associated with non-Hodgkin's lymphomas, 19,20 certain chemotherapeutic drugs (such as fludarabine, cyclophosphamide, and rituximab), 21 certain hematopoietic stem cell transplants, 22 autoimmune diseases such as Sjogren syndrome, 23 kidney transplants, 24 certain solid organ malignancies, 25 and pregnancy. 26 Similarly, our 18 DAT-positive respondents reported that their hemolytic anemia was associated with acute leukemia status post-bone marrow transplant, myelodysplastic syndrome, and sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the PLS, other factors may lead to hemolysis after organ transplantation 13‐15 . In this context it is known that immunosuppressive drugs cause immune alterations and may trigger autoimmunity.…”
Section: Discussionmentioning
confidence: 99%